UPAYA PENINGKATAN HASIL BELAJAR BAHASA INGGRIS SISWA DENGAN MODEL PEMBELAJARAN ACTIVE LEARNING - Huraiyah Huraiyah (Universitas Pendidikan Mandalika, 2015)
This study aims to improve the learning outcomes of the English language by applying the active learning model at SMPN 14 Mataram. The research method used is classroom action research with research subjects, namely students of class IX-E totaling 25 students. Data collection tools used were observation and assessment sheets. Analysis of research data using qualitative and quantitative descriptive analysis. The results of this study indicate that the lecture or conventional method is less effective in increasing student achievement in understanding the material of the report text on English subjects. By applying this method students appear to be more active in learning and enthusiastic in learning increases, the classroom atmosphere becomes lively and there is The increase in learning outcomes is quite good. From the results of each cycle obtained in the first cycle the class average value obtained by students was 64.87, in the second cycle it was 78.12.